Art of memoir [compact disc, unabridged] - Karr, Mary (Harper Collins Publishers, 2015)
For thirty years Karr has also taught the form, winning graduate teaching prizes for her highly selective seminar at Syracuse, where she mentored such future hit authors as Cheryl Strayed, Keith Gessen, and Koren Zailckas. In this, she synthesizes her expertise as professor and therapy patient, writer and spiritual seeker, recovered alcoholic and 'black belt sinner', providing a unique window into the mechanics and art of the form that is as irreverent, insightful, and entertaining as her own work in the genre.